Global conservation and management of biodiversity in developing countries: An opportunity for a new approach - Adenle, Ademola A.; Stevens, Casey; Bridgewater, Peter (Environmental Science & Policy, 2015)
•There is urgent need for increased biodiversity conservation and management in developing countries.•Biodiversity strategy requires a “whole-of-government approach” to achieve the objectives of CBD.•Better planning, raising awareness as well as funding is key to biodiversity conservation in developing countries. The twelfth Conference of the Parties for the Convention on Biological Diversity (CBD) meets in the Republic of Korea, 6–17 October 2014. That meeting marks the half-way point for implementation of the decade-long set of targets (the Aichi Targets) agreed at the tenth Conference of the Parties (Nagoya, Japan, October 2010), and poses a real test for the parties. We contend it also offers considerable opportunity to redefine ways and means for funding and awareness raising for the conservation and management of biodiversity, especially in developing countries. Using the adopted, but as yet poorly implemented, mechanism of National Biodiversity Strategy and Action Plans (NBSAPs) we argue much can be accelerated to ensure that by 2020 the Aichi Targets will have been implemented and that the vision that “by 2050, biodiversity is valued, conserved, restored and wisely used, maintaining ecosystem services, sustaining a healthy planet and delivering benefits essential for all people” will be within reach. On the other hand, lack or loss of momentum on outreach about, and funding for, biodiversity especially in the global south could see continued declines in the health of ecosystems.